Service Design Capabilities - Morelli, Nicola; de Götzen, Amalia; Simeone, Luca (Springer Nature, 2021)
This open access book discusses service design capabilities in innovation processes, and provides a framework that guides design students, practitioners and researchers towards a better understanding of operational aspects of service design processes. More specifically, it revisits service designers capabilities in light of the new roles that have opened up in innovation processes on different scales. After years of being inadequately defined, the professional profile of service designers is now taking shape. Today private and public institutions recognize service designers as essential contributors to their innovation and development processes. What are the capabilities that characterize a service designer? These essential capabilities are what service designers should acquire in their education and can sell when looking for a job.
English
Keywords: Research & development management; Production engineering; Service industries; Innovation/Technology Management; Manufacturing, Machines, Tools, Processes; Services; Business and Management; Machines, Tools, Processes; Industries; service design; value creation interaction; value creation infrastructure; Service System Design; innovation; Design capabilities; open access; Research & development management; Industrial applications of scientific research & technological innovation; Production engineering; Hospitality & service industries